Analytical Calculation for Time-varying Mesh Stiffness of Articulated Supported Rack-Gear Based on Potential Energy Principle - Tang Liang; Chen Zaigang; Yang Jizhong; Chen Zhihui (Jixie chuandong)
Gear-rack transmission is an important mechanical transmission mode and the time-varying mesh stiffness of gear-rack is one of the main excitation sources, which has an important effect on the vibration and noise level of the mechanical system. An analytical calculation method for time-varying mesh stiffness of articulated supported rack-gear transmission is proposed based on the potential energy principle, which aims to solve the problem of efficient and accurate analytical calculation for gear-rack mesh stiffness. Then, the time-varying mesh stiffness of a gear-rack transmission with different parameters is calculated using this method. By comparing the calculated results with that derived from the finite element model, the correctness of the established analytical calculation model is verified. In addition, the effect of the vertical clearance, pressure angle and rack length on the time-varying mesh stiffness of gear-rack is analyzed using this analytical calculation model. The results indicate that the analytical calculation model can accurately calculate the time-varying mesh stiffness of the gear-rack transmission, and it can provide theoretical support for the dynamic analysis of gear-rack transmission system.